The Royal Air Force North Polar Research Flights, 1945 - Winfield, R. H. (Polar Record, 1947)
The R.A.F. North Polar Research Flights were made during the month of May 1945 by the four-engined aircraft Aries . In sixteen days these flights covered more than 24,000 miles, the greater part of which lay within the Arctic Circle. The more important objects of the expedition were to investigate the problems of navigation in high latitudes, to make a magnetic survey in the region of the North Magnetic Pole, to test the reliability of magnetic compasses in its vicinity, and finally to observe the effects of polar flying on aircrew. The Aries was built as a standard Lancaster heavy bomber, identical with those aircraft which fought the battles of the Ruhr and Berlin. The aircraft was modified slightly for polar flying. The range was increased to about 5000 miles by fitting extra petrol tanks in the bomb bays. Extra speed was obtained by removing the camouflage paint and by streamlining the nose and tail. Since the three heavy gun turrets and armour plating were not required, room was found for a further petrol tank in the nose, and a second astrodome amidships. The latter was used for taking sextant readings. Additional space in the tail was welcomed for stowing the emergency equipment.